Case study 11: The use of camera traps to monitor medium to large mammals in HCVAs, Wilmar Oil Palm Plantation, Miri, Sarawak - Mohd-Azlan, Jayasilan; Lok, Lisa Choy Hong; Ng, Ginny Siew Ling; Chin, Sing Yun; Marcie Elene, Marcus Jopony; Wong, James Tai Hock (HCV Malaysia Toolkit Steering Committee, 2021)
Wilmar has a long-term collaboration with UNIMAS since 2013 to conduct biodiversity monitoring (including camera trapping for monitoring mammals) at its oil palm estates in the Miri Division in Sarawak. The biodiversity monitoring sites consist of three HCVAs that are located within the estates. These forested areas are designated as HCVAs as they contain substantial proportions of remnant native biodiversity. Camera trapping has been extensively used in wildlife research as it is highly effi cient and cost-effective for monitoring mammals (Tobler et al., 2008; Rovero et al., 2014), especially in the case of tropical rainforests where species can be cryptic and elusive in nature (Azlan, 2006). Three mammalian surveys via camera trapping were conducted in the Wilmar Oil Palm Plantation, Miri, Sarawak in years 2013-2014, 2014-2015 and 2018-2020. Study sites consisted of three High Conservation Value Areas (HCVAs) that are located within the estates of Saremas 1, Saremas 2 and Segarmas. Bukit Durang is the largest HCVA measuring 989.9ha, Segarmas HCVA is 147.9ha and the smallest is Saremas 1 HCVA at 116.3ha (see accompanying map). Bukit Durang HCVA is classifi ed as HCV 1 while Saremas 1 and Saremas 2 HCVAs are classed as HCV 4. These forests were designated as HCVAs as they contain substantial proportions of remnant native biodiversity. The HCVs are managed by Wilmar’s Eco Management Unit (EMU) under the Sustainability Division and fi nanced by the individual estates. Wilmar Oil Palm Plantation is certifi ed by MSPO, ISCC and RSPO.